LEGAL CERTAINTY ON THE DEED OF GRANTING MORTGAGE WHICH WAS REGISTERED LATE AT THE NATIONAL LAND AGENCY IN MAKASSAR CITY - Syalwi Afrianti; Farida Patittingi; Muhammad Ilham Arisaputra (El-Iqthisadi, 2022)
Abstract This study aims to analyze the implementation of PPAT obligations in APHT registration and the implications of APHT registered by PPAT more than 7 (seven) working days. This research was conducted using empirical research methods. The data obtained, both primary and secondary data, were categorized according to the type of data. Then the data was analyzed using qualitative methods, namely analyzing data related to the problem under study, then selected based on a logical mind to avoid errors in the data analysis process. The results of this study indicate that: 1) Mortgage registration is carried out by the Land Office by making the Mortgage Land Book and recording it in the Land Rights Book which is the object of the Mortgage Rights and copying the notes on the relevant Land Title Certificate. After the entry into force of PMATR No. 5/2020, APHT registration is done online. Mortgage registration is carried out by means of PPAT submitting APHT and supporting documents to the land office, deed and warkah documents are only submitted in scanned form through the electronic mortgage system and the land office no longer accepts physical documents. 2) The delay in APHT registration will affect the birth of Mortgage Rights. In essence, the laws and regulations provide a time limit for the registration of APHT and other documents with the aim of legal certainty for the guarantee itself and certainty of legal protection for creditors. Keywords: Deed, Mortgage Right, Registration.